Variance Analysis: A Management-Oriented Approach. - Shank, John K.; Churchill, Neil C. (The Accounting Review, 1977)
ABSTRACT: This paper describes and illustrates an approach to teaching variance analysis which the authors have found to be very effective with their students. The approach is based on the dual ideas of profit impact as a unifying theme and a multi-level analysis in which complexity is added sequentially, one layer at a time. The analysis stops when additional complexity is not outweighed by additional "actionable" insights.